Systemic Therapy of Advanced/Metastatic Breast Cancer - Current Evidence and Future Concepts - Liedtke, Cornelia (Breast Care (Basel), 2016)
Systemic therapy of metastatic breast cancer may include chemotherapy, endocrine therapy, and targeted therapies (e.g., antibody-based approaches). These agents may be employed alone or in combination based on the patient's breast cancer subtype. Therefore, characterization of the disease phenotype is necessary and may include biopsy of the metastatic site. Novel therapeutic approaches include immunologic therapies, PARP inhibitors, PI3K inhibitors, and CDK4/6 inhibitors, which are currently under investigation in clinical trials.